PERAN MODAL SOSIAL DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT PETANI TEMBAKAU DI KABUPATEN WONOSOBO - Budhi Cahyono (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2014)
Dimensions of social capital described everything that makes people allied to achieve a common goal based on unity, and bounded by the values and norms that grow and obeyed, as well as the social relations inherent in social structures and social networks in a community that creates wide range of social obligations, creating a climate of mutual trust, bring information channels, and establish norms and social sanctions for members of the community (Coleman , 1999). However, Fukuyama ( 2000) says that not necessarily the norms and shared values are guided by reference behave, act, and behave it automatically becomes social capital. However, only the norms and shared values based on trust. Where trust is build from expectations, honesty, and cooperative behavior emerging from within a community based on shared norms shared by its members. The population consisted of tobacco farmers, community leaders, and government officials from eight districts and rural villages are selected as samples. While the number of respondents were 104 people , consisting of 80 tobacco farmers, 16 community leaders, 16 of the village, sub-district and 2 devices. Variables research includes the study of economic, socialcultural, demographic, tobacco farmers, and the effectiveness of social capital. Data collection using focus group discussions ( FGD ) with the respondent, and field observations. The results showed that the values of trust in social capital is dominant as the basis for rural communities to be used as based on improvement of other functions, such as increased respect and mutual benefit. Problems in the optimization problem concerning the nature of social capital, human resource issues, and management issues. The main problems to optimize the role of social capital in rural areas need the support of various stakeholders, and the demands of rural communities regarding the importance of mentoring programs to improve the competence of rural communities by improving farming skills, and improve agricultural diversification. In addition, the need for transformational leadership support to improve the optimization of the role of social capital .Keywords : social capital, welfare, transformational leadership, mentoring